If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying k + -12 = 3 Reorder the terms: -12 + k = 3 Solving -12 + k = 3 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + k = 3 + 12 Combine like terms: -12 + 12 = 0 0 + k = 3 + 12 k = 3 + 12 Combine like terms: 3 + 12 = 15 k = 15 Simplifying k = 15
| 0=12x^2+5x-29 | | -3x^2+5x-24=0 | | 12-(7-3)= | | -2-2(4z-4)=5(6z-8)-1 | | 4/9=10/n | | 5x-24-24-11x=3x+24+3x | | -5ab+10bc= | | 40=16-.4x | | 40+=16-.4x | | -14=(s+12)/6 | | 3/4x+1/3y=1 | | 40+0=16-.4x | | -u-17=-4u+1 | | 1/9(8t-6)=t-6/18 | | 40+.3=16-.4x | | a/5-2=13 | | 1/2x+4=-2/3+1/2 | | 12.8-0.5y+2.9-0.7y=14-1.2y-3.1 | | (-3)x^2+343=0 | | p+6=2p+10 | | -3/4(x-3/4)=-3/8(x+3) | | 27x=x^2 | | 4/7x+2/3x=13 | | x(3x+1)=30 | | f(t)=5t^2+4t | | 10(20m+11)= | | 4x-1+2x+x+3=30 | | -7(t+5)=21 | | 8/x=1/4-x | | (1/2)x^2-8=0 | | 8x+8x=7x | | 8x+14=10x+8 |